Pembentukan Pendidikan Karakter Melalui Pembiasaan Pagi Di SD N Pedurungan Lor 02 Semarang - Ana Fitria; Muhammad Prayito; Rasiman Rasiman; Hartati Hartati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The purpose of the research is to find the strength of the character education of honesty and responsibility of students at SD Negeri Pedurungan Lor 02 Semarang, the efforts made by the school and parents to increase the strength of honest character and responsibility through morning habituation. The type of research conducted is qualitative research with the results written containing a report of data quotations to provide a presentation of the results. The research was conducted at SD N Pedurungan lor 02 Semarang with the subject of 4th-grade students and teachers. Data collection techniques were taken from interviews, observation, and documentation. The results of this study are the implementation of strengthening integrity character education through morning habits according to the plans made by the teacher. The teacher checks the contents of the attendance board that has been provided. The teacher also communicates well in determining rules and sanctions for students if they violate them, while parents monitor children's activities at home when doing habituation activities. To make students honest and responsible for what they do, teachers and parents have strategies to improve the characters by giving rewards or strict sanctions if they violate them.